2022
DOI: 10.1088/1755-1315/1041/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

In-silico screening of inhibitor on protein epidermal growth factor receptor (EGFR)

Abstract: The screening process to detect early-stage lung cancer is injurious to a patient’s survival. Fortunately, there are natural compounds that have been acknowledged to possess anticancer properties, work as the protein binding inhibitors of lung cancer promotors: EGF and EGFR. The study aims to identify inhibitors of EGFR protein binding. Assessments were accomplished based on several parameters related to EGFR proteins, such as pathways, protein activity, conformational changes, and numerous information using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…The best validity score of protein 3D structure quality has Ramachandran Favoured more than 50% and Ramachandran Outlier less than 15%, better if the score of Ramachandran Favoured bigger and Ramachandran Outlier smaller. 16,33,34 Thus, protein 3D structure of 3CLpro receptor had the best quality.…”
Section: Resultsmentioning
confidence: 97%
“…The best validity score of protein 3D structure quality has Ramachandran Favoured more than 50% and Ramachandran Outlier less than 15%, better if the score of Ramachandran Favoured bigger and Ramachandran Outlier smaller. 16,33,34 Thus, protein 3D structure of 3CLpro receptor had the best quality.…”
Section: Resultsmentioning
confidence: 97%
“…The degree of binding affinity influences biological activity when binding to proteins. 28 In this study, biological activity was demonstrated by inhibiting SARS-CoV-2 and body cells through interaction of bioactive compounds and target proteins. 29 The bond affinity value that used in this study is the smallest because it indicates the presence of additional stability and higher inhibition activity performed by the ligand towards the protein target.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is a less preferred bond to Arg60 that requires further research into its role in this interaction. 42 Meanwhile, ellagic acid likely has bonds with some catalytic residues such as hydrogen bonds with Gln110 as well as vdw bonds with Gln107 and Asn151.…”
Section: Resultsmentioning
confidence: 99%